Peningkatan Nasionalisme Mahasiswa melalui Literasi Budaya Batik di TMII - Isna Muhammad Fathoni; Hadi Rohyana; Ilham Jaya; Maspupah, Maspupah; Widi Astuti (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service is motivated by the importance of increasing nationalism among students through understanding local culture, especially batik as an Indonesian cultural heritage. The purpose of this activity is to increase students' awareness and appreciation of the values ​​of nationalism through batik cultural literacy at Taman Mini Indonesia Indah (TMII). The partners in this activity are S1 PGSD students of the Faculty of Education, Bani Saleh University. The methods used in this community service are socialization, training, and direct practice related to the history, philosophy, and techniques of making batik. The activities are carried out in several stages, namely providing a pre-test, delivering material about the history and philosophical meaning of batik, demonstrating batik making, and student reflection on the importance of batik in building national identity. The last stage is providing a post-test to measure the participants' abilities after socialization. The results of the community service show an increase in students' understanding of the cultural values ​​of batik, which is indicated by an increase in test scores. The average score during the pre-test was 5.78 points and increased to 8.39 points during the post-test. Thus, batik cultural literacy can be an effective strategy in instilling nationalism among students as the next generation of the nation.